The dictionary of body language : a field guide to human behaviour - Navarro, Joe, 1953- (Thorsons, 2018)
After reading The Dictionary of Body Language, you'll have a new ability to read other people's true intentions, and to adjust your own body presentation so that you can convey the right messages.